RASIONALIS DAN RASIONALISME DALAM PERSPEKTIF SEJARAH - Teng, Muhammad Bahar Akkase (Universitas Hasanuddin, 2016)
This journal discusses about Rationlists and Rationalism viewed from historical perspective.Philosiphical thinking of modern age according to wetern version consists of three periods, i.e. ancientage, middle age, and modern age. Rasionalism is pioneered by Descartes from Paris, so he is calledthe Father of Modern Philosophy. The development of science as the characteristics of modern societyis Rationalism. This school prioritizes ratio to reveal truth. The early founder of rationalism isHeraclitus who believes that ratio is more superior than five senses. The further developmenthappened from 17th century to 18th century. The appearance of rationalism is the willingness ofrationalists to free themselves from scholastic thinking. The figures of rationalists are Rene Descartes( 1596-1650 ), Nicholas Malerbranche (1638-1775), Baruch de Spinoza (1632-1677), (G.W. Leibniz(1646-1716), Christian Wolff (1679-1754), Blaise Pascal (1623-1662).Key words: rationalism, development, figure, history